Is it normal to lead? Evaluating the role of superiority and similarity in leader emergence - Harms, Peter D.; Paterson, Ted A.; Wood, Dustin; Fezzey, Tyler N. A. (Frontiers in Organizational Psychology, 2024)
Attempts to explain the leader emergence process have resulted in several seemingly contradictory assertions about who attains power and influence in groups. As such, this study pioneers a novel integration of the two dominant explanations of leader emergence: superiority (trait-based perspective) and similarity (social identity perspective). We posit that the two primary aspects of non-normality – uniqueness and strangeness – have opposing relationships with leader emergence in groups. Utilizing a sample of 308 participants in seven social organizations, this study provides general support for a relationship between the non-normality dimensions and leader emergence, particularly when evaluations are made by peers. Additionally, we demonstrate that non-normality evaluations predict leader emergence above and beyond evaluations of the Big Five. This research lays the groundwork for a new era in leadership research that embraces the duality of individual traits and social perceptions, paving the way for a more nuanced and effective approach to leader emergence within dynamic group settings.